Inflation News and Euro Area Inflation Expectations - Garcia, Juan Angel (IMF Working Papers; Working Paper ;, 2018)
Do euro area inflation expectations remain well-anchored? This paper finds that the protracted period of low (and below-target) inflation in the euro area since 2013 has weakened their anchoring. Testing their sensitivity to inflation and macroeconomic news, this paper expands existing results in two key dimensions. First, by analyzing all available (advanced) inflation releases. Second, the reactions of expectations are investigated at daily, time-varying and intraday frequency regressions to add robustness to our conclusions. Results point to a significant impact of inflation news over recent years that had not been observed before in the euro area.